1998
DOI: 10.1038/3987
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a newly discovered cellular anti-HIV-1 phenotype

Abstract: Animal cells have developed many ways to suppress viral replication, and viruses have evolved diverse strategies to resist these. Here we provide evidence that the virion infectivity factor protein of human immunodeficiency virus type 1 (HIV-1) functions to counteract a newly discovered activity in human cells that otherwise inhibits virus replication. This anti-viral phenotype is shown by human T cells, the principal in vivo targets for HIV-1, and, based on our present understanding of virion infectivity fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
175
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 248 publications
(184 citation statements)
references
References 36 publications
7
175
0
2
Order By: Relevance
“…This discovery traces back to original observations that deletion of the HIV-1 vpu gene results in a 5-10-fold 4 The abbreviation used is: SIV, simian immunodeficiency virus. decrease in virus release from infected T cells without impairing the expression of other viral proteins (33).…”
Section: Restriction By Particle Tethering: Bst-2/tetherin Integral Mmentioning
confidence: 97%
See 1 more Smart Citation
“…This discovery traces back to original observations that deletion of the HIV-1 vpu gene results in a 5-10-fold 4 The abbreviation used is: SIV, simian immunodeficiency virus. decrease in virus release from infected T cells without impairing the expression of other viral proteins (33).…”
Section: Restriction By Particle Tethering: Bst-2/tetherin Integral Mmentioning
confidence: 97%
“…23). An excellent recent example is provided by studies on nat- ural simian immunodeficiency virus (SIV) 4 infection of four African green monkey (SIV agm ) subspecies (24). As expected, the Vif protein of each SIV agm strain degrades the APOBEC3G protein of its respective host.…”
Section: Restriction By Hypermutation: Apobec3 Dna Deaminasesmentioning
confidence: 99%
“…It was shown that the propagation of HIV-1 strains lacking the accessory protein Vif is suppressed in a number of nonpermissive cells and that this block was due to expression of the cytidine deaminase APOBEC3G (A3G). 7,8 Further studies revealed that A3G induces massive C3 U deamination of single stranded retroviral DNA, resulting in DNA degradation or lethal G3 A hypermutation. [9][10][11] Interestingly, A3G can also interfere with the HBV life cycle in cotransfected cells.…”
mentioning
confidence: 99%
“…Several reports (9,10,12,(14)(15)(16)(17)(18)(19) have shown that mutations in the recently defined HCCH motif impair Vif function. In one report (19), Vif C114 (amino acid numbering used hereafter refers to the HIV-1 HXB2 Vif sequence) was proposed to constitute part of a cysteine protease active site involved in gp41 processing.…”
mentioning
confidence: 99%